Os salőes de arte contemporânea de Santo André : de 1968 a 1985 - Negrisolli, Douglas (2011)
This research deals with the beginning of the Halls of Contemporary Art in Santo André, in the Greater ABC region in São Paulo when he was conceived at the time and that the event is inserted in the calendar of Arts nationally. The Halls of Contemporary Art in Santo André collaborate with the construction of the art scene noting the national production and becoming an important disseminator of the art forward processes of democratization in the period of military rule. The work consists the construction of a historiography of art fairs including artists winners of the "Purchase Awards" from its inception in 1968 when it occurred, until 1985 when the Halls are still in the midst of discussions on political and social epicenter of the construction of a new democracy. Social movements in the region ABC Paulista and collaborate to culminate the process of democratization and reach its peak when the National Congress approves and guarantees universal suffrage direct elections for mayor and president